Social Connectedness among Emerging Adults in a State University in Western Visayas - Andrada, Analee; Doromal, Araceli (Technium Social Sciences Journal, 2024)
Social connectedness plays a crucial role in the lives of emerging adults. Hence, social connectedness assessment is necessary to check their acquisition of the expected competencies. Anchored on Bowlby’s attachment theory and Eysenck theory on nature and nurture, this study profiled the emerging adults’ personality profile and extent of social connectedness in a state university in Western Visayas, Philippines, in terms of school, family, peer, and community relative to sex, academic program, birth order, and family structure. Utilizing the descriptive-correlational approach, a standardized personality inventory and an adapted social connectedness questionnaire were administered to 252 stratified randomly sampled emerging adults, using very great to very poor extent ratings. In data analysis, mean, standard deviation, frequency count, percentage, rank biserial, and eta correlation were employed. Overall, agreeableness has the highest rating. Emerging adults have great extent of social connectedness showing that they often feel cared, trusted, and respected by their professors, classmates, friends, family, and neighbors. Academic program and family structure had significant relationship with social connectedness, where education and science courses and those from intact families had higher rating than their counterparts. With these results, the theories are validated and a proposed enhancement personality development program is recommended to strengthen their social connectedness.